When State Building Backfires: Elite Coordination and Popular Grievance in Rebellion. Issue 4 (20th July 2021) - Garfias, Francisco; Sellars, Emily A.
Abstract: We examine the complementary influence of elite politics, popular grievances, and central government weakness on rebellion. Efforts to strengthen the central state often come at the expense of the elite intermediaries charged with maintaining local political control. By driving a wedge between local elites and the central government, centralizing reforms can reduce intermediaries' willingness to repress mobilization, providing an opening for popular rebellion during both localized and national crises. For a given level of commoner grievance, revolts from below are thus more likely to be attempted and more likely to spread where elites' incentives to enforce order have been diminished. We formalize these ideas and provide supportive evidence using subnational data on rebellion, tax centralization, and drought in colonial Mexico from the late seventeenth century to the War of Independence.